Perovskite Solar Cells: Analysis of Ion‐Diffusion‐Induced Interface Degradation in Inverted Perovskite Solar Cells via Restoration of the Ag Electrode (Adv. Energy Mater. 11/2018). Issue 11 (17th April 2018) - Lee, Hyunho; Lee, Changhee
Abstract : The cover image representing the work presented in article number1702197 by Changhee Lee and Hyunho Lee illustrates a degradation mechanism of perovskite solar cells. Deterioration of perovskite layer produces iodide ions which diffuse and accumulate at the Ag electrode interface, causing the degradation of the performance of perovskite solar cells. Iodide ions (yellow drops) are released from the aged polycrystalline perovskite layer (cracked, deserted land) and form clouds that block the sun, limiting charge extraction (thunder) from the perovskite layer to Ag electrode.